DEVELOPING STUDENT WORKSHEET BASED ON MISSOURI MATHEMATICS PROJECT MODEL BY USING THINK-TALK-WRITE STRATEGY OF CLASS VIII - Reny Wahyuni; Efuansyah Efuansyah; Sukasno Sukasno (Jurnal Infinity, 2020)
This study aims to develop the worksheet based Learning Model Missouri Mathematics Project using Think Talk Write Strategy on cube and cuboid material, and to find out the quality of the worksheet developed in terms of validity and practicality. Subjects in this study are students of class VIII SMP N 11 Lubuklinggau in the even semester of the 2018/2019 school year. This research is a development research that refers to the 4-D development model (Define, Design, Develop, and Disseminate). Based on the analysis results, it was found that the quality of worksheets developed was based on the assessment of 3 validators, the validity aspect was in the Good category with an average score of 3.99, while the quality of worksheets from the practical aspect was in the Very Practical category with an average score of 0.903.